Pengaruh Motivasi dan Gaji Karyawan Terhadap Produktivitas pada PT Integra Indocabinet di Sidoarjo - Pius Owen Krismanto Wiwoho; Is Fadhillah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to examine “The effect of work motivation and salary on employee productivity performance”. The background of this research is the decline in productivity that occurred at PT Integra Indocabinet in 2012 and during the Covid-19 pandemic. The sample in this study were employees at PT Integra Indocabinet Sedati Sidoarjo East Java, totaling 100 people as respondents taken using the Slovin formula. The sampling technique used in this study is non probability sampling, namely techniques that do not buy opportunities or become samples. By using a questionnaire method 4 Likert scale. From the results of hypothesis testing, it shows that 1) motivation has no significant positive effect on employee performance when the t statistical test is carried out, 2) salary has a significant positive effect on employee performance, 3) motivation and salary on productivity simultaneously have a significant positive effect.